Dry and Wet Events in Andean Populations of Northern Peru: A Case Study of Chachapoyas, Peru - Rascón, Jesús; Gosgot Angeles, Wildor; Quiñones Huatangari, Lenin; Oliva, Manuel; Barrena Gurbillón, Miguel Ángel (Frontiers in Environmental Science, 2021)
Climate change and population growth have heavily impacted the ecosystem’s water resources, essential for anthropogenic activities. These also apply to the Andean city of Chachapoyas, located in the north of Peru, which has gone through a substantial population increase in recent years, therefore increasing its water demand. This research aimed to assess dry and wet events from 1981 to 2019 that have taken place in Chachapoyas, by applying the Standardized Precipitation Index (SPI), and the Standardized Precipitation Evapotranspiration Index (SPEI). These events were periodically characterized, and the index relationship was determined at different timescales. The SPI and SPEI indices were calculated at the city’s only weather station for timescales of 3, 6, 12, and 24 months using climatic data. The indices showed a remarkably consistent behavior for timescales of 12 and 24-months detecting an extreme drought event in 1993, while for timescales of 3 and 6-months a severe drought event was detected in the same year. Contrastingly, there has been an increase in extreme wet events in the last decade, hence Chachapoyas is categorized between "moderate drought" and "moderate wet". It should be noted that the indices have a high correlation between them when calculated for the same timescale. The results were statistically significant (p<0.05). Considering the results obtained related to dry and wet events and their relation with economic activities such as environmental management, we can conclude that the SPI and SPEI indices are useful and valuable tools for local and regional governments